FIZIKA FANIDAN LABORATORIYA MASHG‘ULOTLARIDA TAJRIBA NATIJALARINI QAYTA ISHLASH METODIKASI - Kanatbayev, S.S. (SCIENCE and SOCIETY, 2024)
The article analyzes the essence and structure of a physical experiment, as well as the importance of taking into account measurement errors processing and identifying the results of physical experiments in laboratory physics classes.
Keywords: Physical event; laboratory classes; experiment; skills; measurement; processing the results; measurement errors; random errors; systematic errors